Chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode as well as preparation method and application of chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode
By constructing a hierarchical structure oxygen evolution electrode on a nickel mesh substrate and using sulfide and doped iron oxyhydroxide nanosheet clusters, the problems of slow anodic oxygen evolution reaction kinetics and electrode corrosion in seawater electrolysis for hydrogen production were solved, achieving Efficient oxygen evolution and chlorine corrosion resistance.
Patent Information
- Application Number
- CN202411578308.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-07
AI Technical Summary
During the process of electrolysis of seawater hydrogen production, the anode oxygen evolution reaction kinetics are slow, and high concentration of chloride ions leads to electrode corrosion, affecting the efficiency of electrolytic water reaction.
The two-step method of water-heat-engraving to build a hierarchical structured oxygen analysis on the nickel mesh base. Improve catalytic activity and anti -chlorine corrosion performance.
It significantly improves the activity and stability of the catalyst, reduces the corrosion effect of chloride ions, and realizes the performance of efficient oxygen and chlorine resistance in seawater.
Smart Images

Figure CN119352060A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalysis, and in particular relates to a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode and a preparation method and application thereof. Background Art
[0002] As a clean and efficient energy carrier, hydrogen energy has significant advantages in promoting deep decarbonization of energy systems. Among them, green hydrogen generated by water electrolysis technology using renewable energy is regarded as an ideal way to produce hydrogen energy. Compared with the traditional water electrolysis process, seawater electrolysis for hydrogen production has the unique advantages of abundant resources and no reliance on scarce freshwater resources, as well as high hydrogen production efficiency and controllable reaction conditions under alkaline conditions, providing a highly promising option for large-scale production of green hydrogen. However, in the process of hydrogen production by seawater electrolysis, the oxygen evolution reaction occurring at the anode involves a four-electron transfer mechanism, which results in a relatively slow reaction kinetics, becoming one of the key factors restricting the overall hydrogen production efficiency. In addition, the high concentration of chloride ions (Cl - ) will not only induce chlorine oxidation side reactions at the anode, reducing the efficiency of the oxygen evolution reaction, but will also cause serious corrosion to the electrode materials, causing voltage increases and even electrode damage, affecting the electrolysis of water. Therefore, it is particularly important to develop seawater electrolysis oxygen evolution electrodes with high activity and stability.
[0003] Although anode electrodes based on precious metals such as Ir, Ru and their oxides show excellent activity in oxygen evolution reaction, their large-scale industrial application is limited by the scarcity and high cost of precious metal resources. Given that transition metal-based catalysts are abundant in the earth's crust and their physical and chemical properties are easy to control, the development of a transition metal-based oxygen evolution electrode that is resistant to chlorine corrosion, highly active and highly stable has become a key research direction in the field of hydrogen production by seawater electrolysis.
[0004] Studies have shown that by constructing a hierarchical structure and implementing a synergistic strategy of element doping, the utilization rate of catalytic active sites can be effectively improved, spatial charge migration can be promoted, and the energy barrier of the oxygen evolution reaction can be reduced, effectively driving the efficient electrolysis of seawater. Among them, transition metal hydroxides (TMOOHs) can not only improve the oxygen evolution activity, but also give the catalyst excellent resistance to chloride corrosion. In addition, transition metal sulfides have been shown to reconstruct in a strong electrochemical oxidation environment, and the corresponding polyatomic anion sulfate SO will be formed under the application of bias during the anodic oxygen evolution process. 4 2-, migrate and insert into the hierarchical nanostructure to form anion intercalation. The presence of this anion intercalation can effectively inhibit the adsorption of chloride ions on the electrode surface through like-charge repulsion, thereby reducing the corrosion of chloride ions on the catalyst activity. However, the current exploration of the corrosion resistance of catalysts and green, scalable synthesis methods is still insufficient, and it is difficult to meet the urgent needs of the future development of direct seawater electrolysis technology. Therefore, the development of practical anode catalysts that can efficiently evolve oxygen in seawater environments and have chlorine corrosion resistance has become a key research direction. Summary of the invention
[0005] Based on the above background, the purpose of the present invention is to provide a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode and its preparation method and application, which not only has excellent electrocatalytic oxygen evolution performance and stability under alkaline high current conditions, but also exhibits excellent chlorine corrosion resistance in alkaline brine, which is beneficial to the future development of seawater electrolysis.
[0006] To achieve the above object, the present invention adopts the following technical solution: A method for preparing a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode comprises the following steps: (1) After ultrasonic cleaning of the nickel mesh, blow it dry in a nitrogen stream to remove oil and oxides on the surface; (2) Dissolve thiourea in deionized water to obtain a reaction solution, place the nickel mesh NM in the inner tank of a hydrothermal kettle, dropwise add the pre-mixed thiourea solution, heat the hydrothermal kettle for hydrothermal reaction to obtain nickel sulfide Ni 3 S 2 Nanosheet catalysts; (3) Sodium chloride NaCl and ferric chloride FeCl 3 , sodium thiosulfate 2 S 2 O 3 and / or tantalum pentachloride TaCl 5 Dissolve in deionized water to prepare an etching solution, immerse the nickel mesh loaded with nickel sulfide nanosheets prepared in step (2) in the etching solution for etching, and wash the obtained electrode with deionized water and nitrogen N 2 After purging and drying, a nickel mesh-supported modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode was obtained.
[0007] Furthermore, in step (1), the nickel mesh is ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each.
[0008] Furthermore, in step (2), the reaction solution is a 2.5-25 mM thiourea solution.
[0009] Furthermore, in the step (2), the hydrothermal reactor is fully reacted at 100-130° C. for 10-14 hours.
[0010] Furthermore, in step (3), the etching solution contains 1-1.5 M NaCl, 2 mM Na 2 S 2 O 3 、1 mMFeCl 3 and 0-0.02 mM TaCl 5 of solution.
[0011] Furthermore, in the step (3), the nickel mesh loaded with nickel sulfide nanosheets is etched at 40° C. for 8-15 hours to obtain a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode.
[0012] The present invention also provides a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode prepared by the above preparation method.
[0013] The present invention also provides a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode for use in electrocatalytic oxygen evolution reaction and seawater electrolysis to produce hydrogen.
[0014] The present invention adopts a two-step hydrothermal-etching method with mild reaction conditions to construct a sulfide Ni on the surface of the nickel mesh substrate. 3 S 2 A hierarchical oxygen evolution electrode composed of nanosheets and tantalum-doped iron oxyhydroxide FeOOH nanosheet clusters. Through the construction of multi-level interfaces and heteroatom doping, the electrode not only significantly improves the intrinsic catalytic activity, but also exhibits excellent chlorine corrosion resistance.
[0015] Compared with the prior art, the present invention has the following advantages: (1) The present invention uses a nickel mesh with high mechanical strength as a substrate and constructs a self-supporting three-dimensional hierarchical structure electrode through in-situ growth. The hydrophilic nanosheet clusters in this structure have pores of different sizes, which are conducive to the effective diffusion of the electrolyte and promote the rapid release of bubbles when operating at high current density. In addition, the multi-scale pores of the electrode can effectively disperse the voltage and reduce the formation of local hot spots, thereby effectively improving the stability and industrial life of the catalyst.
[0016] (2) The hierarchical structure electrode prepared by the present invention not only provides a large surface area and high-density active sites, but also ensures a strong bonding force between the active material and the substrate, reduces the contact resistance of charge transfer, and ensures rapid mass transfer in the solid-gas-liquid three-phase reaction; at the same time, the local optimization of electron distribution caused by element doping reduces the energy barrier of the catalytic reaction, allowing the electrode to achieve efficient oxygen evolution catalytic reaction at a lower overpotential.
[0017] (3) The chlorine corrosion resistance of the hierarchical oxygen evolution electrode of the present invention is due to the multi-atomic SO generated by the reconstruction of the nickel sulfide in the catalyst intermediate layer. 4 2- Anion intercalation not only activates the oxygen evolution capacity of the FeOOH active layer, but also effectively prevents the anion Cl - Deep corrosion resistance, achieving excellent oxygen evolution stability in seawater. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to fully explain the characteristics, objectives and advantages of the present invention, the specific implementation scheme of the present invention will be introduced and explained in more detail below in conjunction with the relevant drawings.
[0019] Figure 1 This is a scanning electron microscope image of the catalyst on the electrode surface prepared in Examples 1-4.
[0020] Figure 2 This is the XPS overall spectrum of the electrode surface catalyst prepared in Examples 1-3.
[0021] Figure 3 This is a high-magnification spectrum of the catalyst on the electrode surface prepared in Example 1-3.
[0022] Figure 4 Oxygen evolution polarization curves of the electrode prepared in Examples 1-3 and a commercial nickel mesh electrode in 1 M KOH solution.
[0023] Figure 5 These are stability test curves of the electrode prepared in Example 1 in 1 M KOH solution and 1 M KOH+0.5 M NaCl solution, respectively. DETAILED DESCRIPTION
[0024] The following will further elaborate on the technical solutions in the embodiments of the present invention through the accompanying drawings. The embodiments described here are only exemplary and do not represent all implementations of the present invention. The protection scope of the present invention is not limited to these examples, but has a wider scope of application.
[0025] Example 1
[0026] (1) Cut the nickel mesh into 1×2 cm 2 The small pieces were then ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each, and then blown dry in a nitrogen stream to remove surface oil and oxides.
[0027] (2) Mix 0.25 mmol of thiourea with 40 mL of deionized water to prepare a 6.25 mM thiourea reaction solution. Place the nickel mesh NM sheet in the inner tank of the hydrothermal kettle and slowly drip the pre-mixed thiourea solution to ensure that it evenly covers the entire surface. The hydrothermal reaction is set at 120°C for 12 hours. After cooling, the nickel mesh-loaded nickel sulfide Ni 3 S 2 / NM catalyst.
[0028] (3) Weigh NaCl and FeCl 3 、Na 2 S 2 O 3 and TaCl 5 , prepared to a concentration of 1.25 M NaCl, 2 mM Na 2 S 2 O 3 , 1 mM FeCl 3 and 0.1 mM TaCl 5 The nickel mesh is loaded with nickel sulfide Ni 3 S 2 / NM catalyst was immersed in the etching solution (immersion area was 1 × 1 cm 2 ), etched at 40 °C for 12 h to obtain the modified iron oxyhydroxide / sulfide Ta-FeOOH / Ni supported on the nickel mesh. 3 S 2 / NM electrode.
[0029] Example 2
[0030] (1) Cut the nickel mesh into 1×2 cm 2 The small pieces were then ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each, and then blown dry in a nitrogen stream to remove surface oil and oxides.
[0031] (2) Mix 0.25 mmol of thiourea with 40 mL of deionized water to prepare a 6.25 mM thiourea reaction solution. Place the nickel mesh NM sheet in the inner tank of the hydrothermal kettle and slowly drip the pre-mixed thiourea solution to ensure that it evenly covers the entire surface. The hydrothermal reaction is set at 120°C for 12 hours. After cooling, the nickel mesh-loaded nickel sulfide Ni 3 S 2 / NM catalyst.
[0032] (3) Weigh NaCl and FeCl 3 and Na 2 S 2 O 3, prepared to a concentration of 1.25 M NaCl, 2 mM Na 2 S 2 O 3 and 1 mMFeCl 3 The nickel mesh is loaded with nickel sulfide Ni 3 S 2 / NM catalyst was immersed in the etching solution (immersion area was 1 × 1 cm 2 ), etched at 40 ° C for 12 hours to obtain nickel mesh supported iron oxyhydroxide / sulfide FeOOH / Ni 3 S 2 / NM electrode.
[0033] Example 3
[0034] (1) Cut the nickel mesh into 1×2 cm 2 The small pieces were then ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each, and then blown dry in a nitrogen stream to remove surface oil and oxides.
[0035] (2) Mix 0.5 mmol of thiourea with 40 mL of deionized water to prepare a 12.5 mM thiourea reaction solution. Place the nickel mesh NM sheet in the inner tank of the hydrothermal kettle and slowly drip the pre-mixed thiourea solution to ensure that it evenly covers the entire surface. The hydrothermal reaction is set at 130°C for 10 hours. After cooling, the nickel mesh-loaded nickel sulfide Ni 3 S 2 / NM catalyst.
[0036] Example 4
[0037] (1) Cut the nickel mesh into 1×2 cm 2 The small pieces were then ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each, and then blown dry in a nitrogen stream to remove surface oil and oxides.
[0038] (2) Mix 0.25 mmol of thiourea with 40 mL of deionized water to prepare a 6.25 mM thiourea reaction solution. Place the nickel mesh NM sheet in the inner tank of the hydrothermal kettle and slowly drip the pre-mixed thiourea solution to ensure that it evenly covers the entire surface. The hydrothermal reaction is set at 120°C for 12 hours. After cooling, the nickel mesh-loaded nickel sulfide Ni 3 S 2 / NM catalyst.
[0039] (3) Weigh NaCl and FeCl 3 、Na 2 S 2 O3 and TaCl 5 , prepared to a concentration of 1.25 M NaCl, 2 mM Na 2 S 2 O 3 , 1 mM FeCl 3 and 0.2 mM TaCl 5 The nickel mesh is loaded with nickel sulfide Ni 3 S 2 / NM catalyst was immersed in the etching solution (immersion area was 1 × 1 cm 2 ), etched at 40 °C for 12 h to obtain the modified iron oxyhydroxide / sulfide Ta-FeOOH / Ni supported on the nickel mesh. 3 S 2 / NM electrode.
[0040] The catalysts prepared in Examples 1-4 above were characterized by morphology, structure and chemical properties.
[0041] Figure 1 The scanning electron microscope images of the catalysts on the electrode surfaces prepared in Examples 1-4 are shown respectively. Figure 1 In a), Ni is uniformly grown on the nickel mesh substrate. 3 S 2 Nanosheets. This sheet structure can serve as an active layer and also provide an effective pore structure channel for the rapid diffusion of electrolytes. Example 2 ( Figure 1 b) Ni can be observed on the surface 3 S 2 The FeOOH nanosheet clusters with thinner and flower-like morphology are generated on the nanosheet. This hierarchical structure can not only enhance the interaction between the oxyhydroxide and the sulfide, but also increase the active surface area and provide more catalytic active sites. Figure 1 c) in the figure shows that the introduction of an appropriate amount of Ta atoms promotes the formation of denser nanosheet clusters. This hierarchical structure can consolidate the interaction between oxyhydroxides and sulfides and provide a larger active surface and more catalytic active sites. Figure 1 In d), it can be found that excessive Ta atom doping causes the catalyst surface to become rough, and may even lead to a decrease in the mechanical strength of the catalyst and a fragile structure.
[0042] Figure 2 This is the XPS general spectrum of Examples 1-3. Through full spectrum analysis, the existence of Ni, Fe, Ta, O, S in Example 1, Ni, Fe, O, S in Example 2, and Ni, O, S in Example 3 were verified respectively.
[0043] Figure 3The high-resolution spectrum of Ni 2p at 855.2 eV (Ni 2p 3 / 2 ) and 872.8 eV (Ni 2p 1 / 2 ) corresponds to the two spin-orbit peaks near Ni 2+ . S 2- S 2p 3 / 2 and S 2p 1 / 2 The characteristic peaks of are located at 161.6 eV and 162.9 eV, while the characteristic peak at 167.4 eV corresponds to SO 4 2- . SO 4 2- The presence of FeOOH is due to surface oxidation, which can effectively activate the FeOOH active layer in the anode reaction of seawater electrolysis and prevent Cl - The aggregation on the hierarchical structure surface improves the electrode's resistance to chlorine corrosion. The characteristic peaks of Fe 2p at 711.5 eV and 724.2 eV correspond to Fe 3+ 2p 3 / 2 and Fe 3+ 2p 1 / 2 By comparing the spectra of Ni 2p, Fe 2p and S 2p in Examples 1-3, it can be found that with the construction of the hierarchical nanosheet interface and the introduction of Ta, the binding energy of Ni and S moves toward the negative direction, and Fe 2p shifts to a higher binding energy. This shows that the synergistic effect of interface optimization coupling element doping can effectively promote the transfer of electrons and improve the intrinsic conductivity of the catalyst.
[0044] The electrochemical workstation was used to test the electrocatalytic oxygen evolution performance of the electrodes and nickel mesh prepared in Examples 1-3 in a three-electrode system. 1 M KOH alkaline solution was used as the electrolyte, a graphite rod was used as the counter electrode, and a Hg / HgO electrode was used as the reference electrode. The catalyst area prepared in Examples 1-4 was 1 cm 2 The electrode was used as the working electrode for testing. The potentials of all electrodes were iR compensated and converted to reversible hydrogen electrode (RHE) potentials according to the Nernst equation. The polarization curve scan rate was set to 5 mV s -1 .
[0045] For the oxygen evolution catalyst, the current density was 100 mA cm -2 and 500 mA cm -2 The corresponding overpotential is an important indicator for judging the performance of the catalyst and the feasibility of industrial application. Figure 4 From the polarization curves, it can be observed that for the commercial nickel mesh electrode (Ni / NM), 100 mA cm -2The corresponding overpotential is 430 mV. After the nickel sulfide intermediate layer is introduced, the overpotential of Example 3 is reduced. After further multi-level interface optimization, Example 2 shows excellent overpotential (100 mA cm -2 247 mV; 500 mA cm -2 After introducing the appropriate Ta element to coordinately regulate the electronic structure, Example 1 exhibits the best oxygen evolution performance (100 mA cm -2 230 mV; 500 mA cm -2 is 283 mV).
[0046] In order to test the stability of the oxygen evolution electrode of Example 1 at a high current density, a current density of 500 mA cm-2 was used in a 1 M KOH electrolyte. -2 Furthermore, in order to test the chlorine corrosion resistance of the electrode of Example 1 in seawater, 1 M KOH + 0.5 M NaCl and a current density of 500 mA cm -2 Simulated alkaline seawater electrolysis was carried out under conditions of 3.5 % to explore its chlorine corrosion resistance.
[0047] Figure 5 The stability test diagrams of Example 1 in 1 M KOH solution and 1 M KOH + 0.5 M NaCl salt solution were tested at 500 mA cm -2 The results show that Example 1 has good stability under current density of 500 mA cm -2 Driven by the current density, the performance did not change significantly in 1 M KOH solution for 360 hours. In 1 M KOH + 0.5 M NaCl salt solution, the voltage of Example 1 did not change significantly after 200 hours.
[0048] It should be clear that the above embodiments are only examples for clearly explaining the present invention and are not limited to the above specific implementations. Within the framework of the claims, those skilled in the art may adjust or make equivalent changes to these features and embodiments without changing the essential content of the present invention. The specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. All equivalent changes and modifications made in accordance with the scope of protection of the patent application of the present invention shall be deemed to fall within the scope of protection of the present invention.
Claims
1. A method for preparing a chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode, characterized in that: The following steps are involved: (1) After ultrasonic cleaning of the nickel mesh, blow it dry in a nitrogen stream to remove oil and oxides on the surface; (2) dissolving thiourea in deionized water to obtain a reaction solution, placing a nickel mesh in an inner tank of a hydrothermal kettle, dripping the pre-mixed thiourea solution, heating the hydrothermal kettle for a hydrothermal reaction to obtain a nickel sulfide Ni3S2 nanosheet catalyst; (3) Sodium chloride, ferric chloride, sodium thiosulfate and / or tantalum pentachloride are dissolved in deionized water to prepare an etching solution, the nickel mesh-supported nickel sulfide nanosheets prepared in step (2) are immersed in the etching solution for etching, and the obtained electrode is washed with deionized water and dried by nitrogen purge to obtain a nickel mesh-supported modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode.
2. The method for preparing a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode according to claim 1, characterized in that: In step (1), the nickel mesh is ultrasonically cleaned in ethanol, acetone, 1 M hydrochloric acid solution and deionized water for 15 minutes each.
3. The method for preparing a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode according to claim 1, characterized in that: In step (2), the reaction solution is a thiourea solution with a concentration of 2.5-25 mM.
4. The method for preparing a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode according to claim 1, characterized in that: In step (2), the hydrothermal reactor is fully reacted at 100-130°C for 10-14 hours.
5. The method for preparing a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode according to claim 1, characterized in that: In step (3), the etching solution is a solution containing 1-1.5 M NaCl, 2 mM Na2S2O3, 1 mMFeCl3 and 0-0.2 mM TaCl5.
6. The method for preparing a chlorine corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode according to claim 1, characterized in that: In step (3), the nickel mesh loaded with nickel sulfide nanosheets is etched at 40° C. for 8-15 hours to obtain a modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode resistant to chlorine corrosion.
7. A chlorine-corrosion-resistant modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the modified iron oxyhydroxide / sulfide hierarchical structure oxygen evolution electrode resistant to chlorine corrosion as claimed in claim 7 in electrocatalytic oxygen evolution reaction and hydrogen production by seawater electrolysis.
Citation Information
Patent Citations
High-performance iron-doped nickel- or cobalt-based amorphous oxyhydroxide catalyst prepared by room temperature method, and research thereof on high-efficiency hydrogen production by electrolyzing water
CN112808274A
Preparation method of foam nickel oxygen evolution electrode material with multi-stage array structure and product and application of foam nickel oxygen evolution electrode material
CN115369435A
Supported ferronickel-based oxygen evolution electrode and preparation method and application thereof
CN116180102A
Activated peroxymonosulfate catalytic membrane as well as preparation method and application thereof
CN117815939A
Nickel-based alloy composite electrode having gradient component structure, and preparation method therefor and use thereof
WO2024021403A1